The chemistry of episodic accretion. Issue Volume 15:Issue S350(2019) (April 2019) - Rab, C.; Elbakyan, V.; Vorobyov, E.; Postel, A.; Güdel, M.; Dionatos, O.; Audard, M.; Kamp, I.; Thi, W.-F.; Woitke, P.
Abstract: Episodic accretion is an important process in the evolution of young stars and their surroundings. A consequence of an episodic accretion event is a luminosity burst, which heats the protostellar environment and has a long lasting impact on the chemical evolution of the disk and envelope of young stars. We present a new model for the chemistry of episodic accretion based on the 2D radiation thermo-chemical disk code ProDiMo. We discuss the impact of an episodic accretion burst on the chemical evolution of CO and its observables. Furthermore we present a model for the outbursting source V883 Ori where we fitted available observational data to get an accurate physical structure that allows for a detailed study of the chemistry.